Evaluating Quality of Contraceptive Counseling: An Analysis of the Method Information Index. Issue 1 (21st January 2019) - Chang, Karen T.; Mukanu, Mulenga; Bellows, Ben; Hameed, Waqas; Kalamar, Amanda M.; Grépin, Karen A.; Gul, Xaher; Chakraborty, Nirali M.
Abstract: The Method Information Index (MII) is calculated from contraceptive users' responses to questions regarding counseling content—whether they were informed about methods other than the one they received, told about method‐specific side effects, and advised what to do if they experienced side effects. The MII is increasingly reported in national surveys and used to track program performance, but little is known about its properties. Using additional questions, we assessed the consistency between responses and the method received in a prospective, multicountry study. We employed two definitions of consistency: (1) presence of any concordant response, and (2) absence of discordant responses. Consistency was high when asking whether users were informed about other methods and what to do about side effects. Responses were least consistent when asking whether side effects were mentioned. Adjusting for inconsistency, scores were up to 50 percent and 30 percent lower in Pakistan and Uganda, respectively, compared to unadjusted MII scores. Additional questions facilitated better understanding of counseling quality.